2017
DOI: 10.1037/ser0000131
|View full text |Cite
|
Sign up to set email alerts
|

Community-based implementation of trauma-focused interventions for youth: Economic impact of the learning collaborative model.

Abstract: This study investigated the economics of the learning collaborative (LC) model in the implementation of Trauma-Focused Cognitive-Behavioral Therapy (TF-CBT), an evidence-based intervention for traumatic stress in youth. We evaluated the cost-effectiveness of the LC model based on data from 13 LCs completed in the southeastern United States. Specifically, we calculated cost-effectiveness ratios (CERs) for two key service outcomes: (1) clinician TF-CBT competence, based on pre- and post-LC self-ratings (n = 574)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
28
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(30 citation statements)
references
References 31 publications
2
28
0
Order By: Relevance
“…Studies of Learning Collaboratives focused on client outcomes have found that this method is associated with improved engagement in behavioral health services (Cavaleri et al, 2006(Cavaleri et al, , 2007(Cavaleri et al, , 2010Rutkowski et al, 2010), including initiating (Cavaleri et al, 2006) and sustaining (Cavaleri et al, 2007) gains in initial appointment attendance rates. It also has been associated with improvements in children's behavioral support services in schools (Stephan, Connors, Arora, & Brey, 2013) and trauma-focused service providers (Dopp, Hanson, Saunders, Dismuke, & Moreland, 2017;Lang, Franks, Epstein, Stover, & Oliver, 2015).…”
Section: Consultation and Supervision Strategiesmentioning
confidence: 99%
“…Studies of Learning Collaboratives focused on client outcomes have found that this method is associated with improved engagement in behavioral health services (Cavaleri et al, 2006(Cavaleri et al, , 2007(Cavaleri et al, , 2010Rutkowski et al, 2010), including initiating (Cavaleri et al, 2006) and sustaining (Cavaleri et al, 2007) gains in initial appointment attendance rates. It also has been associated with improvements in children's behavioral support services in schools (Stephan, Connors, Arora, & Brey, 2013) and trauma-focused service providers (Dopp, Hanson, Saunders, Dismuke, & Moreland, 2017;Lang, Franks, Epstein, Stover, & Oliver, 2015).…”
Section: Consultation and Supervision Strategiesmentioning
confidence: 99%
“…A pre-post analysis of the impact of scaling up MAP in LA County demonstrated significant improvements in client outcomes (Southam-Gerow et al, 2014). While the evidence for MAP as a system is limited, it is built on the deep and well-established literature of EBPs for delivery in community mental health systems (Chorpita, Daleiden, and Collins, 2014 (Cohen, Mannarino, and Deblinger, 2016), TF-CBT has extensive empirical evidence supporting its ability to reduce PTSD, depressive symptoms, and behavioral problems among children ages 3-18 who have experienced different traumas (e.g., Allen and Hoskowitz, 2017;Dopp et al, 2017;Lang and Connell, 2017;Lang et al, 2015;Roundfield and Lang, 2017;Wamser-Nanney and Steinzor, 2017). It has been implemented across the globe in a wide variety of settings.…”
Section: Fsp Programs For Youth and Adultsmentioning
confidence: 99%
“…LC models may be effective in improving clinicians' networks of advice, and serve as a means of informal support throughout implementation (Bunger et al, 2016). Compared to other training methods, the LC is costly at approximately $19,000 per clinician (Dopp, Hanson, Saunders, Dismuke, & Moreland, 2017). A cost-effectiveness analysis revealed that the LC model may be less cost-effective than other training approaches in improving clinician skill; however, the subsequent changes in client outcomes were highly costeffective (Dopp et al, 2017).…”
Section: Trainingmentioning
confidence: 99%
“…Compared to other training methods, the LC is costly at approximately $19,000 per clinician (Dopp, Hanson, Saunders, Dismuke, & Moreland, 2017). A cost-effectiveness analysis revealed that the LC model may be less cost-effective than other training approaches in improving clinician skill; however, the subsequent changes in client outcomes were highly costeffective (Dopp et al, 2017). Another study found that the LC model was ineffective at increasing provider use of preventive services (Solberg et al, 2000).…”
Section: Trainingmentioning
confidence: 99%